Digital inclusion of secondary schools' subject teachers in Bolivia - Popova, Iskra; Fabre, Gabriela (International journal of education and development using information and communication technology, 2017)
The government of Bolivia planned to introduce information technology in secondary education through establishing computer labs in schools and through granting each subject teacher a laptop. This initiative was tested for the first time in 2012 with three public schools in La Paz. Most of the subject teachers have never used a computer before. The Swedish Program for ICT in Developing Regions (SPIDER) supported teachers' training in basic digital skills. This was not sufficient for the teachers to adopt the technology in their daily practice. Within a follow-up research project a constraints driven model for overcoming the barriers teachers faced was developed and applied. The aim of this paper is to provide an overview of the whole process of digital inclusion with focus on the design and implementation of this model. Teachers' adoption of the technology and changes in their skills, attitudes and beliefs were assessed through the analysis of the qualitative data obtained in focus group discussions and observations, as well as through the quantitative data collected through a longitudinal survey. The results show that the adopted model proved to be a successful complement to the government policy. From persons intimidated by the laptops, the subject teachers became confident users of digital technology capable of creating numerous educational units and interactive teaching tools.